Palynological and physicochemical characteristics of three unifloral honey types from central Argentina - Naab, O.A.=700 1 Tamame, M.A.; Caccavari, M.A.
(En, Es)
Ilus., 60 ref.
Keywords: CENTAUREA; POLINIZACION; PALINOLOGIA; PROPIEDADES FISICO-QUIMICAS; MIEL; PROCEDENCIA; BOTANICA; PROSOPIS; ARGENTINA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH